Pengaruh Gaya Kepemimpinan dan Beban Kerja Terhadap Produktivitas Kerja Karyawan pada PT. Pelayaran Nasional Indonesia (Persero) Cabang Makassar - Musa, Chalid Imran; Pratiwi Musa, Kartika Septiary (CV. Lafadz Jaya, 2026)
Employee productivity is a crucial factor in supporting organizational success. This productivity can be influenced by various managerial factors, including leadership style and workload. This study aims to analyze the influence of leadership style and workload on employee productivity at PT Pelayaran Nasional Indonesia (PELNI) Makassar Branch. This study employed a quantitative approach with a descriptive-associative design. The population in this study was all 39 employees of PT PELNI Makassar Branch, therefore, the sampling technique used was saturated sampling. Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis techniques used included multiple linear regression, partial t-tests, simultaneous t-tests, and the coefficient of determination. The results showed that leadership style had a positive and significant effect on employee productivity, with a t-value of 11.730 and a significance level of 0.000. Meanwhile, workload had no significant partial effect on employee productivity, with a significance level of 0.074. Simultaneously, leadership style and workload significantly influence employee work productivity with a calculated F value of 257.153. The coefficient of determination value of 93.5% indicates that employee work productivity can be explained by leadership style and workload, while the rest is influenced by other factors outside the research model. Thus, leadership style is the dominant factor that influences employee work productivity. Therefore, companies need to improve the quality of effective, communicative, and supportive leadership in order to maintain and increase employee work productivity.